Genetic variation for leaf trichome density and its association with sucking insect-pests incidence in Asiatic cotton - Grover, Gomti; Kaur, Baljinder; Pathak, Dharminder; Kumar, Vijay (The Indian Journal of Genetics and Plant Breeding, 2016)
Trichomes on the plant body are known to impartÂ  resistance/susceptibility to various insect-pests. An intra Gossypium arboreum F2 population between aÂ  trichomeless mutant PAUFL 1 and its wild type counterpart was developed to assess the distribution of trichomes on young and mature leaves, and to correlate the trichome density with the sucking insect-pests incidence. Based on pooled data for the years 2011 and 2012, mean trichome count for 552 F2plants was found to be 47.52 and 90.09 (on 28.27 mm2) for mature and young leaves, respectively. A range of 0-185 and 0-218 trichomes was observed for mature and young leaves, respectively. Significant positive correlation (r = 0.83*) was obtained between trichome density of young and mature leaves. Higher trichome density was observed on young leaves. A positive association between young leaf trichome density and whitefly population was recorded which indicates that higher trichome density is favourable for whitefly incidence and vice versa. However, no correlation between the trichome density of young leaves and jassid population was observed.